PEMETAAN RANTAI NILAI IKAN PELAGIS KECIL DI KOTA AMBON - Yolanda MTN Apituley; Dionisius Bawole; Imelda KE Savitri; Friesland Tuapetel (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2018)
This research was taken in Ambon (Latuhalat and Laha) and in Central Maluku Regency (Waai) in May – July 2018. It was aimed at mapping the value chain of small pelagic fish in Ambon through: 1) mapping of product, financial and information flows and 2). analysis of percentage distribution of small pelagic fish caught. The data used in this study was primary and secondary data, and analyzed by using value chain analysis. The results show that small pelagic fish marketing chain in Ambon consisted of six models with five actors. Each chain is formed due to the conditions and situation of market, resulted by the influencing of catches of fishermen and traders' capital. The broker plays an important role in marketing small pelagic fish in the market and obtaining 10% of the fishermen's catch that can be distributed, both to retailers and cold storage. Fish caught by the fishermen is still fresh in general when arrives in the consumers, because the fishing area is not too far, the market distance with the production centers is also quite close and in general fishermen and traders have understood the importance of maintaining product quality. Even so, the role of the Government in providing marketing facilities and infrastructure is needed so that modern market conditions can be applied in marketing fresh fish in Ambon.